Potentiality of light source and predator for controlling brown planthopper - Sardar, M; Khatun, MR; Islam, KS; Haque, MT; Das, G (Progressive Agriculture, 2020)
Experiments were conducted at the net house and laboratory of the Entomology Division of Bangladesh Institute of Nuclear Agriculture (BINA) to determine the effectiveness of four light sources for light trapping, and performance of three predators for controlling brown plant hopper, Nilaparvata lugens (Stal.).The light intensity and sources were 30-50 lux (candle light), 80-100 lux (kerosene lamp), 180-200 lux (bulb) and 380-400 lux (energy saving lamp). The predators, ladybird beetle, carabid beetle and wolf spider, Light traps of 380-400 lux from energy saving lamp showed maximum effect in reducing the pest brown planthopper. Other light sources had little effect on brown planthopper. Light source of 30-200 lux reduced only a few brown planthopper. The predator wolf spider, Lycosa pseudoannulata consumed all the prey individuals of Nilaparvata lugens in three days exposure period indicating its high predation potentiality. Performance of ladybird beetle, Micraspis discolor was moderate and the carabid beetle, Ophionea indica was poor in controlling brown planthopper. The findings of these experiments indicate that light trapping with a source of 380-400 lux, predation by Lycosa pseudoannulata are the promising options in reducing brown planthopper population successfully and it could be an important part of IPM that is essential for the sustainable management of this deleterious brown planthopper in rice cultivation. Progressive Agriculture 30 (3): 275-281, 2019